Merchant Empowerment at Kedonganan Culinary Tourism Center in Preventing COVID-19 - Desak Putu Citra Udiyani; Pande Ayu Naya Kasih Permatananda; Anny Eka Pratiwi (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2022)
Along with the development of pandemic situation which entered the new normal era and successful vaccination of COVID-19, community activities in Bali's tourism centers began to gradually recover, including Kedonganan Beach. However, the risk of COVID-19 transmission remains high due to congested community activities and decreased of health protocols. The solutions and methods offered in this community service are COVID-19 and health protocols refreshment, health assistance and counseling, digital payment socialization, and the provision of hand sanitizers and masks to prevent COVID-19. The implementation of this PKM activity has been going well, seen from the attendance and enthusiasm of the participants, and there has been an increase in participants' knowledge and attitudes regarding the prevention of COVID-19. Through this activity, participants are expected to be an example for the community and keep discipline in implementing health protocols.